Synthesis of Si-containing macro-RAFT agent for the water-borne polyacrylate polyurethane with anti-graffiti coating applications. (December 2020) - Zheng, Xumin; Cai, Zhengchun; Lyu, Zhengwei; Chen, Yongkang; Ji, Yongxin
Highlights: A polymerizable macro-RAFT agent was synthesized and engaged in emulsion polymerizations. Introduce silicone into acrylate polymer by RAFT polymerization. Crosslinking strength affects the performance of the coating film. Polyacrylate-polyurethane has excellent hydrophobicity and anti-fouling property. Abstract: A new water-borne anti-graffiti polyacrylate (WAPA) was synthesized from the Si-containing macro-RAFT agent and functional acrylate monomers. After the cross-linking of a water-borne isocyanate agent with the WAPA for curing during the film cast, the two-component anti-fouling Si-containing polyacrylate polyurethane (WAPAU) was prepared. The structure and properties of the macro-RAFT agent were characterized by FT-IR, GPC and critical micelle concentration analysis. The integration of silicone in the polymers was confirmed by FT-IR and SEM-EDX analysis. The influence of S, S ' -bis(α, α ' -dimethyl-α ' ' -acetic acid)-trithiocarbonate (BDATT) dosage, silicone content, crosslinking density on the properties of emulsions and coating films were investigated, which revealed that the properties of emulsion and coating films were optimal when the amount of BDATT was 0.5 w% and the hydroxyl value of polyacrylate was 160. In addition, changes in silicone content greatly affect the performance of coatings.